2023
DOI: 10.1097/pr9.0000000000001061
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of sleep-promoting pharmacotherapy in patients with chronic pain: a systematic review and meta-analysis

Abstract: Dysregulation of sleep heightens pain sensitivity and may contribute to pain chronification. Interventions which consolidate and lengthen sleep have the potential to improve pain control. The main objective of this systematic review was to examine the effects of sleep-promoting pharmacotherapy on pain intensity in patients with chronic pain. Multiple electronic databases were searched from inception to January 2022 to identify relevant randomized controlled trials (RCTs). Two independent reviewers screened tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…Previous studies have suggested an interrelationship between sleep disturbance and chronic pain. 28 , 29 , 31 Sleep disturbances can lead to detrimental psychological and behavioral effects, such as increased depressive and anxiety symptoms, which exacerbate pain. Conversely, increased pain stimulates the sympathetic nervous system and increases the inflammatory response, causing sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested an interrelationship between sleep disturbance and chronic pain. 28 , 29 , 31 Sleep disturbances can lead to detrimental psychological and behavioral effects, such as increased depressive and anxiety symptoms, which exacerbate pain. Conversely, increased pain stimulates the sympathetic nervous system and increases the inflammatory response, causing sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases have been reported in which insomnia was resolved through cognitive behavioral therapy and chronic pain control in collaboration with these professionals. 29 , 30 , 31 , 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of low quality (downgraded due to imprecision) presented by Andersson et al [29] suggests that 4 to 8 weeks of melatonin treatment reduces pain intensity compared with a placebo. The analgesic effect is confirmed in the work of Ahmad et al [6].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain and insomnia share a close relationship, mutually influencing each other, with numerous reports exploring this connection. [7][8][9][10][11][12] Insomnia affects 10% to 15% of the general population, [11] and research indicates that clinical insomnia is prevalent in over half of the patients with chronic pain, surpassing general population rates. [8] Many individuals with chronic pain struggle with falling asleep or experience sleep disruptions due to pain and insomnia.…”
Section: Introductionmentioning
confidence: 99%